A Secured Clinic Booking System with Multi Factor Authentication - jaafar, sara; A. Hamid, Isredza Rahmi (Applied Information Technology And Computer Science, 2023)
Online Booking system is a software platform where user do not use phone tag and emails to book their sessions. Phone tag is a scenario where two parties contacted each other by using telephone calls or messages. Dr. Hannani Clinic’s existing system implements the online booking system. However, the systems did not have proper security mechanisms to authenticate the user. The proposed Secured Clinic Booking system allows patients to book their appointment online with multi-factor authentication. We apply multi-factor authentication that consists of strong password, One Time Password (OTP) and CAPTCHA. This project uses an object-oriented approach and PHP programming language. The proposed system is able to secure the clinic booking system. Thus, the integrity of the online booking information is protected.